2020
DOI: 10.3390/jcm9040906
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/Valsartan Induces Global Cardiac Reverse Remodeling in Long-Lasting Heart Failure with Reduced Ejection Fraction: Standard and Advanced Echocardiographic Evidences

Abstract: Sacubitril/valsartan reduces mortality in heart failure with reduced ejection fraction (HFrEF) patients, partially due to cardiac reverse remodeling (RR). Little is known about the RR rate in long-lasting HFrEF and the evolution of advanced echocardiographic parameters, despite their known prognostic impact in this setting. We sought to evaluate the rates of left ventricle (LV) and left atrial (LA) RR through standard and advanced echocardiographic imaging in a cohort of HFrEF patients, after the introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 22 publications
8
33
1
Order By: Relevance
“…24 This tendency was also reported in a small retrospective study of patients with HFrEF treated with ARNI: the patients with LV reverse remodelling tended to have a shorter duration of HFrEF. 25 In the present study, we could not determine the duration of HFrEF due to the retrospective study design, but we observed that non-ischaemic HFrEF aetiology was associated with early reverse remodelling. Considering the potential association between the duration of HFrEF and LV reverse remodelling, it could be assumed that the patients with ischaemic aetiology of HFrEF in our study might have a longer duration of HFrEF.…”
Section: Clinical Implications Of Early Reverse Remodellingmentioning
confidence: 57%
“…24 This tendency was also reported in a small retrospective study of patients with HFrEF treated with ARNI: the patients with LV reverse remodelling tended to have a shorter duration of HFrEF. 25 In the present study, we could not determine the duration of HFrEF due to the retrospective study design, but we observed that non-ischaemic HFrEF aetiology was associated with early reverse remodelling. Considering the potential association between the duration of HFrEF and LV reverse remodelling, it could be assumed that the patients with ischaemic aetiology of HFrEF in our study might have a longer duration of HFrEF.…”
Section: Clinical Implications Of Early Reverse Remodellingmentioning
confidence: 57%
“…Recently, Castrichini et al demonstrated that the introduction of sac/val in HFrEF, despite a long history of disease, provides a global LV and LA reverse remodeling in more than 25% of cases, both at standard and advanced echocardiographic evaluations, after a median follow-up of 9 months. However, there was not significant improvement in right heart functional parameters (Castrichini M, et al, 2020). On the contrary, an observation from the Danua Heart Failure Registry reported that in HFrEF patients the treatment with sac/val improved not only LV echo parameters but also allowed an increase in TAPSE and decrease in s-PAP, thus indicating a positive effect on right ventricle function, however the analysis was limited to 12 months without any information on a longer observation (Correale M, et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Three clinical studies and a metanalysis showed a further improvement of cardiac reverse remodelling with SV compared to ACEi or ARBs [7] , [8] , [9] , [10] . Other clinical studies confirmed long term [11] , [12] , [13] , [14] , [15] and short term [16] , [17] , [18] , [19] , [20] improvement in left ventricular ejection fraction (LVEF). SV treatment could induce also an improvement in atrial dimensions [7] , [10] , [13] , [14] , [15] , [19] , mitral regurgitation (MR) [9] , [16] , left ventricular mass (LVM) index [8] , [10] , [17] , diastolic function [7] , [15] , [16] , left ventricle end-systolic volume (ESV) [7] , [10] , [13] , [14] , [15] , [16] , [17] , [19] , [20] and end-diastolic volume (EDV) [7] , [9] , [10] , [13] , [15] , [16] , [17] , [19] , [20] , and right ventricle function [14] , [20] .…”
Section: Introductionmentioning
confidence: 74%
“…Given the impact on hard outcomes showed in the PARADIGM-HF [5] trial, and on the basis of other numerous real-life studies still confirming efficacy and safety performances, the introduction of SV among the treatment options of HFrEF has completely overturned the pharmacological approach to this condition. However, the studies conducted so far did not fully clarify the effects of SV on cardiac function and myocardium reverse remodelling, with results sometimes discordant [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] . Our study analysed the impact of SV therapy on echocardiographic and clinic parameters of HFrEF outpatients previously treated with an optimal individualized pharmacological therapy which included ACEIs or ARBs, BBs and in most patients MRAs.…”
Section: Discussionmentioning
confidence: 99%